Effects of fault transmissivity on the potential of fault reactivation and induced seismicity: Implications for understanding induced seismicity at Pohang EGS. (March 2021) - Wassing, B.B.T; Gan, Q.; Candela, T.; Fokker, P.A.
Highlights: Fault transmissivity effected fault reactivation and seismicity during injection in Pohang EGS. Fault reactivation is impacted by transmissvity of faults and damage zone. Understanding of seismicity response upon injection requires the incorporation of poroelastic effects. Abstract: Enhanced Geothermal Systems (EGS) involve hydraulic stimulation of the permeability of deep low-permeable rock formations. This causes the reactivation and opening of pre-existing natural fracture networks and the formation of new fractures. During hydraulic stimulation, injection pressures at the bottom of the injection well can reach overpressures of up to several tens of MPa. The associated rise in reservoir pressures may trigger felt induced seismicity, as large-scale critically stressed fault structures can be reactivated. We here employ a 3D hydro-mechanical model coupling the software codes of TOUGHREACT and FLAC3D and combine it with Dieterich's formulation for the rate of earthquake nucleation, to create a conceptual model to simulate the effect of stimulation activities on fault Coulomb stressing and associated induced seismicity rates. We discuss the effect of the hydromechanical properties such as fault and damage zone transmissivity and elastic properties on the relative contribution of pore pressure diffusion versus poroelasticity to fault loading. Our modelling approach shows that poroelastic effects can significantly contribute to fault loading, specifically in cases of low fault transmissivity. In this context, we discuss the potential contribution of poroelasticity to the occurrence of seismicity on a previously unmapped sealing fault associated to hydraulic stimulation at the Pohang EGS site in the Southeast of Korea. Our study demonstrates that a quantitative understanding of the stress response and induced seismicity upon injection operations such as the hydraulic stimulation at Pohang requires the incorporation of both pore pressure diffusion and poroelastic effects.